2009
DOI: 10.1007/s12070-009-0031-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of magill forcep in retrieval of foreign body coin

Abstract: Children swallow coins more than any other object. Many methods for removal of impacted coins at the upper end of the oesophagus are enumerated in literature, each having it's own merits and demerits. This retrospective study in 100 consecutive paediatric patients presents a magill forcep technique for removal of coins under inhalational anaesthesia using Mc-Intosch laryngoscope. Intubation and rigid endoscopy both were avoided, thereby minimizing hospital stay and cost of treatment. This also decreases the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Statistically they showed it to be more applicable in younger age group (0-6 years). 22 In our case we found no difficulty in using it in an adult patient. Takrouri et al reported an interesting case of a pin-ended earring got stuck in the hypopharynx of a child where they used MFT to remove it under general anaesthesia uneventfully but a small mucosal tear occurred at the pin entry site and chest complications subsequently.…”
Section: Asymptomatic Pointed Foreign Body In the Hypopharynxsupporting
confidence: 40%
See 1 more Smart Citation
“…Statistically they showed it to be more applicable in younger age group (0-6 years). 22 In our case we found no difficulty in using it in an adult patient. Takrouri et al reported an interesting case of a pin-ended earring got stuck in the hypopharynx of a child where they used MFT to remove it under general anaesthesia uneventfully but a small mucosal tear occurred at the pin entry site and chest complications subsequently.…”
Section: Asymptomatic Pointed Foreign Body In the Hypopharynxsupporting
confidence: 40%
“…This is known as 'Magill forceps technique'(MFT) and noted as one of the extra-anaesthesia uses of Magill forceps. 22 Singh et al studied 100 consecutive paediatric patients of impacted coin at upper end of the oesophagus where they used MFT under inhalational anaesthesia using Macintosh laryngoscope and concluded that this technique was at par with rigid endoscopy in terms of efficacy, safety and complication rate with reduced hospital stay and cost of treatment. Statistically they showed it to be more applicable in younger age group (0-6 years).…”
Section: Asymptomatic Pointed Foreign Body In the Hypopharynxmentioning
confidence: 99%
“…This was in contrast to another Children's Hospital, where half of the cases were endotracheally intubated and solely in those patients, muscular blocking agents were regularly used. While some authors of case series report to use just deep sedation without intubation or usage of muscular blocking drugs, 18,19 others perform the procedures under endotracheal intubation. 16 However, at the hospital where endotracheal intubation with neuromuscular blockade was used more often, the average duration of the procedure was longer (difference not significant).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Singh et al, they have used MFT under inhalational anaesthesia using Macintosh laryngoscope to remove coin from upper end of oesophagus from 100 paediatric patients, they have concluded that this technique is better than rigid endoscopy in terms of efficacy, safety and complication rate with reduced hospital stay and cost of treatment. 20 In our study, we have used Magill's forceps technique (MFT) using Macintosh laryngoscope in 106 cases and rigid esophagoscopy in remaining 27 cases. In 8 cases we could not retrieve coin successfully by using above methods and these cases were referred to surgery for further management.…”
Section: Discussionmentioning
confidence: 99%